Strategi Guru dalam Menerapkan Pembelajaran STEAM melalui Proyek Pembuatan Kincir Air menggunakan Botol Bekas pada Siswa Sekolah Dasar - Tiara Rahmawati; Lina Herlina (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2026)
This study aims to examine teachers’ strategies in implementing STEAM based learning through a project of making a waterwheel using recycled plastic bottles in elementary school students, as well as to analyze its impact on students’ engagement and skills. The research employs a qualitative approach with a descriptive method, while data are collected through observation, interviews, and documentation during the learning process. The results indicate that teachers’ strategies in the planning, implementation, and evaluation stages play a crucial role in determining the success of STEAM implementation. At the planning stage, teachers are able to design integrated learning by considering students’ characteristics and real life contexts. During the implementation stage, the learning process becomes active through project based activities in which students are involved in designing, constructing, and testing the waterwheel collaboratively. The integration of science, technology, engineering, arts, and mathematics is clearly reflected and interconnected within the learning activities. This study also finds improvements in students’ engagement, critical thinking skills, creativity, and collaboration. However, several challenges remain, including time limitations, differences in students’ abilities, and limited facilities. Overall, project based STEAM learning using simple and recycled materials proves to be effective in creating meaningful learning experiences that are relevant to the demands of the 21st century.